Acute symptomatic seizures secondary to autoimmune encephalitis and autoimmune‐associated epilepsy: Conceptual definitions. (16th June 2020) - Steriade, Claude; Britton, Jeffrey; Dale, Russell C.; Gadoth, Avi; Irani, Sarosh R.; Linnoila, Jenny; McKeon, Andrew; Shao, Xiao‐Qiu; Venegas, Viviana; Bien, Christian G.
Abstract: Seizures are a well‐recognized and often prominent manifestation of autoimmune encephalitic syndromes. Progress in detection of pathogenic neural autoantibodies has led to increased awareness of autoimmune causes of seizures. Clinical studies of patients with these autoantibodies have improved our understanding of the seizure characteristics, treatments, and seizure prognosis in these disorders. The International League Against Epilepsy (ILAE) Autoimmunity and Inflammation Taskforce proposes conceptual definitions for two main diagnostic entities: (a) acute symptomatic seizures secondary to autoimmune encephalitis, and (b) autoimmune‐associated epilepsy, the latter of which suggests an enduring predisposition to seizures. Such a distinction is relevant when discussing the pathophysiology, treatment, prognosis, and social consequences of these disorders. We discuss the role of biomarkers in the application of these conceptual definitions and illustrate their use in patients cared for by members of the task force.